1986
DOI: 10.1002/chin.198615098
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Dithioesters by Reaction of Dithioacids or Their Salts with Halides, Aldehydes and Epoxides.

Abstract: Quartäre Ammoniumsalze von Dithiobenzoesäuren reagieren mit Alkyl‐ bzw. Arylhalogeniden oder ‐dihalogeniden unter Bildung von symm. oder unsymm. Dithio‐ bzw. Bisdithioestern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…To our knowledge, no crystal analysis of ammonium dithiocarboxylates has been reported. Since the first isolation of crystalline ammonium dithiocarboxylates in 1972, a variety of ammonium dithiocarboxylates have been prepared. However, quaternary ammonium dithiocarboxylate has been limited to only tetramethylammonium 2-methylpropanecarbodithioate and benzenecarbodithioate and tetraethylammonium 2-hydroxybenzenecarbodithioate 43 and tetrathiooxalates, most likely due to the difficulty of preparation and purification. Their X-ray structural analyses have not been described.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, no crystal analysis of ammonium dithiocarboxylates has been reported. Since the first isolation of crystalline ammonium dithiocarboxylates in 1972, a variety of ammonium dithiocarboxylates have been prepared. However, quaternary ammonium dithiocarboxylate has been limited to only tetramethylammonium 2-methylpropanecarbodithioate and benzenecarbodithioate and tetraethylammonium 2-hydroxybenzenecarbodithioate 43 and tetrathiooxalates, most likely due to the difficulty of preparation and purification. Their X-ray structural analyses have not been described.…”
Section: Resultsmentioning
confidence: 99%
“…The method is applicable to all forms of RAFT agents (i.e., dithioesters, trithiocarbonates, xanthates, and dithiocarbamates) but is mainly used for preparation of RAFT agents containing primary and secondary R groups. RAFT agents with tertiary R are more cumbersome to prepare via this method as nucleophilic substitution on tertiary halides is relatively slow, which results in lower yields of the desired product, requires extended reaction times (e.g., Tables and ), and elimination is a potential complication . Nonetheless, acceptable yields (70–80%) have been reported for some tertiary trithiocarbonates. …”
Section: Raft Agent Synthesismentioning
confidence: 99%
“…The afore‐mentioned synthesized polymer, DTB‐PAS‐diol, includes a dithiobenzoyl structure at the terminal, and this structure derived from the structure of the CTA used here. In general, thiobenzoyl compounds easily hydrolyze in an aqueous medium owing to their low thermodynamic stability (a formation enthalpy for the CS bond is 180 kJ/mol smaller than that for the CO bond). Thiobenzoyl compounds play an important role in RAFT polymerization, and research has reported their stability in an aqueous medium .…”
Section: Resultsmentioning
confidence: 99%